Genetic polymorphisms in non-alcoholic fatty liver disease: Clues to pathogenesis and disease progression - Duvnjak, Marko (The WJG Press and Baishideng, 2009)
The spectrum of non-alcoholic fatty liver disease (NAFLD) ranges from simple steatosis through steatohepatitis to advanced fibrosis and cirrhosis. Although the reason why only a minority of patients develop progressive forms of disease still remains largely unclear, recent research has identified genetic factors as a possible basis for this variation in disease presentation. Most of the studies have been focused on finding associations between advanced disease forms and selected single nucleotide polymorphisms in genes encoding various proteins involved in disease pathogenesis. Although there are many limitations regarding the study design and interpretation of published data, further carefully planned studies together with implementation of new genetic technologies will likely bring new insights into disease pathogenesis and potential benefits to the management of patients with NAFLD.